Humanoid Robot Cooperative Motion Control Based on Optimal Parameterization - Zhong, Qiubo; Li, Yaoyun; Zheng, Caiming; Shen, Tianyao (Frontiers in Neurorobotics, 2021)
The realization of low-energy cooperative motion is one of the key technologies for the complex motion control of humanoid robots. Based on optimal parameters, a control method is adopted to optimize the energy consumption of the cooperative motion of two humanoid robots. A dynamic model that satisfies the cooperative motion is established, and the motional trajectory of two humanoid robots in the process of cooperatively handling objects is planned. Utilizing the control method with optimal parameters, the energy consumption index function is optimized, as the robot keeps stable during the movement. Finally, the effectiveness of the method is verified by simulation and experimentations.